Penerapan Prinsip Syariah Terkait Pembaharuan Hukum Perikatan Pembiayaan Pembangunan Commercial Building Di Atas Tanah Wakaf - Lita, Helza Nova (ZISWAF, 2018)
The growing development of economic transactions based on sharia principles today, requires the existence of legal arrangements that are able to keep abreast of developments, including in the management of waqf assets productively. Based on the provisions of Law Number 41 of 2004 concerning Waqf, that management of waqf assets must be in accordance with sharia principles. In this case also included in the financing agreement for commercial building development on waqf land. This article examines the application of sharia principles in the agreement to finance commercial building development on waqf land. The approach method used is a normative juridical approach method, which is to explore, study and examine secondary data relating to this research material. The use of a juridical approach with consideration of the problem under study revolves around the relevance of a regulation to other regulations. The need for a synergy of various parties' partnership in financing commercial buildings on waqf land. Sharia principles as a provision that must be used under the Waqf Law, provide several sharia principles that can be applied, such as the principle of musharaka and mudharabbah, Istisna', Musyarakah Mutanaqishah, Hawalah, Sukuk (SBSN), and cash waqf. From the results of this study, it can provide input for the development of engagement law reforms originating from Islamic law